Participating life annuities incorporating longevity risk sharing arrangements - Bravo, Jorge (2009)
In this paper we develop a conceptual framework for the payout phase in which annuity providers and policyholders share longevity and investment risks in a flexible way. To be more precise, we develop an participating life annuity product in which systematic longevity risk, i.e., the risk associated with systematic deviations from mortality rates extracted from prospective life tables derived for the Portuguese population, is shared between both counterparties. This will address some of the main demand and supply constraints in annuity markets, namely the inexistence of prospective life tables for the Portuguese population, the perception of unfair pricing, the consideration of bequest motives, adverse selection problems or the lack of financial instruments to hedge against longevity risk. Contrary to traditional GSA's, in which surviving policyholders bear both systematic and unsystematic longevity risk, we devise a contract in which, in exchange for a relatively small premium, annuitants will bear only the part of longevity that exceeds pre-determined thresholds.